MONITORING OF PROFESSIONAL INTEGRATION OF HIGHER EDUCATION GRADUATES: A SURVEY IN THE PROJECT MANAGEMENT DEPARTMENT - Ouafa Saighi,; Salima Rayene Kadri,; Assia Kadri,; Souad Sassi, (International Journal of Innovative Technologies in Social Science, 2024)
The professional integration of graduates is a key indicator of the quality and relevance of university curricula. This paper analyses a tracking review of graduates of the project management course at the University of Constantine 3. It is based on a survey conducted over a number of years among graduates of this course since the first class graduated. This study provides an overview of the program after 13 years.The preliminary results obtained, although partial, reveal a satisfactory rate of employability among graduates, as well as a diversity of choices in terms of sectors of activity and places of work. These observations provide an interesting insight into the career paths of former students. In addition, this longitudinal study provides pertinent points of reflection for the continuous improvement of training offers in order to better respond to the evolving requirements of the labor market and the competencies targeted by employers.